DIVERSITAS EKHINODERMATA (ASTEROIDEA, ECHINOIDEA DAN HOLOTHUROIDEA) DI PERAIRAN PULAU OSI, SERAM BARAT-MALUKU TENGAH - Eddy Yusron; Edward (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2019)
Study of diversity Echinoderms (Asteroidea, Echinoidea and Holothuroidea) at the beach area of Osi Island, Central Maluku. Observation on echinoderms diversity was carried out at the coastal areas in July 2012. The purpose of this study is to get information about the cummunity structure of the echinoderm in the Osi Islands coastal areas, Maluku Tengah. Sampling was conducted by using quadrate transect of 1 m x 1 m. The results of this study showed that there were 16 species of echinoderms, belongs to four species of Asteroidea, five species of Echinoidea and seven species of Holothuroidea. The Holothuroidea were commonly found in the seagrass zone. Based on the data from the three sampling tations, Holothuroidea has the highest density among the other observed biota. The quantitative analysis revealed that the highest diversity and evenness indexes of faunal assemblage was found at tation two (H = 1.117; J = 0.974), while the highest species richness was represented by the Echinoderms from tation one (D = 0.079). Generally, all biota found in this study (14 species) prefer seagrass as microhabitat, nine species occupy sandy areas and eight species inhabit seaweed.